Effects of incentive spirometer training on dyspnea and functional status in patients with long COVID - Yao-Hsiang Chen; Chia-Huei Lin; Ju-Han Liu; Hsin-An Lin; Yu-Shan Hsieh (PLoS ONE, 2026)
Background Since the emergence of Coronavirus Disease 2019 (COVID-19), it has become a global pandemic, profoundly affecting public health and daily life. Many recovering individuals report persistent or recurrent symptoms—fatigue, palpitations, cognitive impairment, shortness of breath, anxiety, and chest discomfort. These lingering effects impair work, daily function, and social interaction, placing a significant burden on individual quality of life and society. Objective This study aims to evaluate the effectiveness of using an induced Incentive Spirometer as a respiratory training tool to relieve long COVID symptoms. Methods This study, conducted from July 1, 2023, to May 11, 2024, at a regional teaching hospital in northern Taiwan, involved participants who had recovered from COVID-19 within the past year and had at least one long COVID respiratory symptom. Participants were assigned to one waiting control group and four experimental groups based on recovery time: within 3 months (Experimental Group 1), 3–6 months (Experimental Group 2), 6–9 months (Experimental Group 3), and 9–12 months (Experimental Group 4). The waiting control group received no interventions, while the experimental groups underwent inspiratory training using an induced Incentive Spirometer three times a week for 6 weeks (30 repetitions per session). Assessments were conducted before and after the intervention. Primary outcomes were the Dyspnoea-12 scale and Post-COVID-19 Functional Status scale. Secondary outcomes included the 6-minute walk distance and CaO₂. Results Ninety participants were enrolled, with five withdrawing, leaving 85 for final analysis. After 6 weeks of intervention, the waiting control group showed no significant changes in dyspnea ( p = 0.463) or post-COVID-19 functional status ( p = 0.343). In contrast, all experimental groups showed significant improvements. Dyspnoea-12 scale scores improved in Experimental Groups 1 ( p < 0.001), 2 ( p = 0.008), 3 ( p = 0.011), and 4 ( p = 0.001). The Post-COVID-19 Functional Status scale also showed improvements in all Experimental Groups (Group 1: p < 0.001, Group 2: p = 0.003, Group 3: p = 0.002, and Group 4: p = 0.011). Significant improvements in 6-min walk distance were observed in some experimental groups, improvements were seen in Experimental Groups 1 ( p < 0.001), 2 ( p = 0.027), 3 ( p = 0.68), and 4 ( p = 0.172). No significant changes in CaO2 were observed (pre-test, p = 0.872 and post-test, p = 0.585). Conclusion Respiratory training using an induced Incentive Spirometer may help alleviate dyspnea and improve post-COVID-19 functional status in individuals with Long COVID. Earlier intervention appeared to yield better outcomes, although improvements were also observed even 9–12 months after infection. However, further studies with comprehensive pulmonary assessments are needed to confirm these findings. Clinical trial number NCT06165835, registered on 9 December 2023.